2016
DOI: 10.1186/s12859-016-0905-0
|View full text |Cite
|
Sign up to set email alerts
|

The exceptional genomic word symmetry along DNA sequences

Abstract: BackgroundThe second Chargaff’s parity rule and its extensions are recognized as universal phenomena in DNA sequences. However, parity of the frequencies of reverse complementary oligonucleotides could be a mere consequence of the single nucleotide parity rule, if nucleotide independence is assumed. Exceptional symmetry (symmetry beyond that expected under an independent nucleotide assumption) was proposed previously as a meaningful measure of the extension of the second parity rule to oligonucleotides. The gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…To analyze dynamic changes in functional levels with increasing degrees of malignancy in the four subtypes, we applied the sliding window approach [ 13 ] to integrate pathway scores for the four subtypes (Figure 9 ). The LOESS fitting algorithm [ 14 ] was used to smooth the data.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To analyze dynamic changes in functional levels with increasing degrees of malignancy in the four subtypes, we applied the sliding window approach [ 13 ] to integrate pathway scores for the four subtypes (Figure 9 ). The LOESS fitting algorithm [ 14 ] was used to smooth the data.…”
Section: Resultsmentioning
confidence: 99%
“…We evaluated dynamic pathway alterations among the different subtypes using the sliding window [ 13 ] and LOESS fitting [ 14 ] methods. The classic functional and disease pathways identified in this study showed functional level differences among the four subtypes, exhibiting primarily linear changes correlated with degree of malignancy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Strand symmetry, also called the second parity rule, exists in almost all modern cellular genomes (genomes in living organisms nowadays on Earth). It is the phenomenon in which the numbers of occurrence of individual nucleotides and oligonucleotides (words) match well and exclusively with those of their respective reverse complements (complementary words) in each genomic DNA strand of sufficient length (e.g., for tetranucleotide GTCA vs. TGAC; for review see Baisnée et al, 2002 ; Forsdyke and Bell, 2004 ; Albrecht-Buehler, 2006 ; Zhang and Huang, 2010 ; Afreixo et al, 2016 ; Shporer et al, 2016 ). As an important feature of genome compositional structures, strand symmetry may persist for higher-order oligonucleotides, while the degree of symmetry decreases with increasing order (see Zhang and Huang, 2008 for example).…”
Section: Introductionmentioning
confidence: 99%